QUASISTATIC GROWTH OF CAVITIES AND CRACKS IN THE PLANE - Bresciani, Marco; Friedrich, Manuel (SIAM Journal on Mathematical Analysis, 2025)
We propose a model for the quasistatic growth of cavities and cracks in two-dimensional nonlinear elasticity. Cavities and cracks are modeled as discrete and compact subsets of a planar domain, respectively, and deformations are defined only outside of cracks. The model accounts for the irreversibility of both processes of cavitation and fracture, and it allows for the coalescence of cavities into cracks. Our main result shows the existence of quasistatic evolutions in the case of a finite number of cavities under an a priori bound on the number of connected components of the cracks.
CRIS-Team Scopus Importer:2025-05-30
Keywords: cavitation; fracture; nonlinear elasticity; quasistatic evolution